PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR OTOMOTIF DAN KOMPONEN PERIODE 2016-2019 - Waluyo Waluyo; Widia Reisya Yulianti (Institut Bisnis Muhammadiyah Bekasi, 2022)
The economy in Indonesia has experienced rapid growth from time to time. To assess the financial performance and achievements of an investor, an investor needs analysis of financial statements as a consideration in determining stock prices. This study aims to determine the financial performance simultaneously and partially on stock prices in automotive and component sub-sector companies listed on the IDX for the 2016-2019 period. Sampling was done by purposive sampling technique to get a representative sample in accordance with predetermined criteria. The number of samples obtained is as many as 10 automotive sub-sector companies for the 2016-2019 period, so a sample of 40 components is obtained. The method used to analyze the data is the method of multiple linear regression analysis and hypothesis testing. The results of the data analysis show that there is a significant effect between CR and ROE partially on stock prices. The t-test (CR) based on the significant value of the CR variable (X1) shows T count > t table of 5.672 > 2.024 and the significance value is 0.000 < 0.05, so statistical hypothesis 1 is related to the partial effect of the CR variable on stock prices, H 0 is rejected and H 1 is accepted, in this case it means that CR has an effect on stock prices.